Anatomical segmentectomy of the pancreatic head along the embryological fusion plane: A case series and a literature review. Issue 18 (May 2018) - Zhu, Chunfu; Jia, Zhongzhi; Zhang, Xudong; Yu, Qiang; Qin, Xihu
Abstract: Rationale: Anatomical segmentectomy of the pancreatic head along the embryological fusion plane (EFP) has been used in the treatment of benign, borderline, and low-grade malignancy neoplasms. However, few studies have reported on the outcomes of this procedure. The aim of this study was to retrospectively assess the outcomes of anatomical segmentectomy of the pancreatic head along the EFP. Patient concerns: We experienced two patients who underwent anatomical segmentectomy of the pancreatic head along the EFP for the treatment of pancreatic cystadenoma. Case 1 was a 69-year-old man presented with upper abdominal pain that had lasted for 3 months. Case 2 was a 52-year-old man presented with upper abdominal pain that had lasted for 1 week. Diagnosis: Both patients were diagnosed of pancreatic cystadenoma. Intervention: Anatomical segmentectomy of the pancreatic head along the EFP was performed. Outcomes: Both patients successfully underwent anatomical segmentectomy of the pancreatic head along the EFP, including ventral segmentectomy and dorsal segmentectomy, and each patient recovered uneventfully. With the inclusion of these 2 cases, there are now a total of 15 cases that have been reported in the literature, including 9 cases of ventral segmentectomy and 6 cases of dorsal segmentectomy. Although pancreatic fistula occurred in 6 of these patients (40%), all of the patients recovered completely without severe complications. Lessons: These results suggest that anatomical segmentectomy of the pancreatic head along the EFP is a safe and feasible procedure for cases of benign pancreatic disease confined to the dorsal or ventral segment of the pancreas.